"I'm Not Touching You. It's The Robot!": Inclusion Through A Touch-Based Robot Among Mixed-Visual Ability Children - Neto, Isabel; Hu, Yuhan; Correia, Filipa; Rocha, Filipa; Nogueira, Joao; Buckmayer, Katharina; Hoffman, Guy; Nicolau, Hugo; Paiva, Ana (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Children with visual impairments often struggle to fully participate in group activities due to limited access to visual cues. They have difficulty perceiving what is happening, when, and how to act-leading to children with and without visual impairments being frustrated with the group activity, reducing mutual interactions. To address this, we created Touchibo, a tactile storyteller robot acting in a multisensory setting, encouraging touch-based interactions. Touchibo provides an inclusive space for group interaction as touch is a highly accessible modality in a mixed-visual ability context. In a study involving 107 children (37 with visual impairments), we compared Touchibo to an audio-only storyteller. Results indicate that Touchibo significantly improved children's individual and group participation perception, sparking touch-based interactions and the storyteller was more likable and helpful. Our study highlights touch-based robots' potential to enrich children's social interactions by prompting interpersonal touch, particularly in mixed-visual ability settings.CCS CONCEPTS* Social and professional topics → Children; People with disabilities; * Human-centered computing → Haptic devices; Empirical studies in HCI.